Comparative Studies of African Traditional Religions - Nwahaghi, Felix N. (Journal of Dharma, 1990)
In Comparative Studies of African Traditional Religions. Ikenga Metuh focuses on the disparate African world-views to determine their similarities and dissimilarities. The book falls thematically into two parts. The first part - which. has been prefaced with a review of the different me- thodologies so far used in the study of African Traditional Religions, definition and sources of African Traditional Religions - studies in detail the African world-views. The author noted that in African world-views. all beings belong to either of two worlds: the visible or invisible. although the beings interact. Metuh examines E.W. Smith's triangular model of the structure of the invisible world as it is conceived by the Bantu speak- ing areas of East and Central Africa: "At the apex was the supreme God. on one side of the triangle were the nature gods and on the other side the ancestors while at the base were the lower magical powers" (p. 65).